2012
DOI: 10.2165/11633450-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Isolated and Integrated ‘Core Stability’ Training on Athletic Performance Measures

Abstract: Background Core stability training, operationally defined as training focused to improve trunk and hip control, is an integral part of athletic development, yet little is known about its direct relation to athletic performance. Objective This systematic review focuses on identification of the association between core stability and sports-related performance measures. A secondary objective was to identify difficulties encountered when trying to train core stability with the goal of improving athletic performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 31 publications
0
50
0
12
Order By: Relevance
“…[16]. Studies that have demonstrated improvement have utilized progressive core-training programs and included both core strength and stability [13, 1719].…”
Section: Introductionmentioning
confidence: 99%
“…[16]. Studies that have demonstrated improvement have utilized progressive core-training programs and included both core strength and stability [13, 1719].…”
Section: Introductionmentioning
confidence: 99%
“…Core stabilization training had a positive effect on the service velocity for young tennis players. Although there are quite a number of scientific researches investigating the relationship between athletic performance and core stabilization, strength and power, the impact of core strength on performance is contradictory (Reed, Ford, Myer, & Hewett, 2012). As it is applied in the present study, while it is accepted as the injury reducing effect of the core stabilization exercises is much more than the core strengthening exercises (Lehman, 2006), findings for athletic influence may not be considered sufficiently.…”
Section: Sonuç Ve öNeri̇lermentioning
confidence: 75%
“…Literatürde atletik performans-core dayanıklılık, kuvvet ve güç ilişkisini araştıran oldukça çok bilimsel araştırmaya rastlansa da sonuçların performansa etkisi tartışmalıdır (Reed, Ford, Myer, & Hewett, 2012). Bu çalışmada olduğu gibi core kuvvetten çok core stabilizasyonu arttırmaya yönelik antrenman uygulamalarının sakatlığı azaltma etkisi kabul edilirken (Lehman, 2006), atletik etkisi için bulgular yeterli kabul edilmeyebilir (Hibbs, Thompson, French, Wrigley, & Spears, 2008).…”
Section: Discussionunclassified
“…etkisinin az olduğu veya olmadığı ortaya koyulsa da (Nesser et al, 2008;Okada, Huxel, & Nesser, 2011;Reed, Ford, Myer, & Hewett, 2012b;Scibek, 1999;Sharrock, Cropper, Mostad, Johnson, & Malone, 2011;Willardson, 2007), bu çalışmanın sonuçları core stabilizasyon antrenmanları ve core stabilizasyon testlerindeki olumlu gelişmenin futbolcuların Stork denge testine yansıdığını ortaya koymaktadır. Stork denge testine ait ön ve son test değerlerin grup içi ve gruplar arası farklılık ve test*grup ilişkisi bulgularına bakıldığında (Tablo 3-Grafik1), her iki ayak için de deney gruplarında %18 ila %67 arasında dengede kalma süresinin arttığı görülmektedir.…”
Section: Bulgularunclassified
“…Son yıllarda core egzersizlere ilgi bir hayli artmış, bu konuda yapılan çalışmalar ile core antrenman-vücut kompozisyonu, gövde stabilizasyonu, atletik performans, sakatlık ilişkisi ve değişimi incelenmeye çalışılmıştır (Reed, Ford, Myer, & Hewett, 2012a). Fakat core stabilizasyon performans ilişkisi oldukça tartışmalıdır (Willardson, 2007;Willson, Dougherty, Ireland, & Davis, 2005).…”
Section: Introductionunclassified